(untitled) (Intellectual Inception: A Multidisciplinary Research Journal of Bhojpur Campus, 2024)
When the Panchayat regime emerged as a new governmental system in Nepal, it brought various developmental projects to elevate the socio-economic condition of the people. However, when it was practically implemented, instead of betterment, the public confronted hardship in celebrating their liberty and autonomy. The society was stratified into different domains, constricting the space for the commoners and limiting their horizon of understanding. In this context, J.B. Tuhure’s song played an important role to narrate the precise story of the folks and make them aware of their position, blasting revolutionary thoughts inwardly in their consciousness. As the songs are suggestive in nature, they are, in fact, counter-voices against the regime and underlying structure of Nepali society, which had to be changed for the emancipation of the subalterns. In this relevance, this research paper explores Tuhure’s three specific songs: Basai Hidne ko Taanti Le, Aama Didi Baini Ho, and Chhora Haru Ho, focusing on how the musicality of these songs create subaltern counterpublics space to construct anti-dominant narrations of the Panchayat regime and how these songs pave the way for the recognition of the marginalized category of people in the stratified societies, where layers of domination persist. Taking Nancy Fraser’s concept of ‘Subaltern Counterpublics Space’ and Christopher Small’s notion of ‘Musicking’ as a theoretical perspective, the paper argues Tuhure’s songs are the spaces where a cluster of subaltern narratives simultaneously occur, challenging the regime and vocalizing the rights for the subordinated. It unravels that Tuhure’s songs are the musicking of subaltern counterpublics spaces, making the public participatory and performative.